AN INTEGRATED APPROACH TO POLYCYSTIC OVARY SYNDROME: DIAGNOSIS, PHARMACOLOGICAL TREATMENT AND BEHAVIOURAL INTERVENTIONS - Aleksandra Dzwonkowska; Paulina Redel (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Polycystic ovary syndrome (PCOS) is an endocrine disorder affecting women of all ages. PCOS is one of the most common causes of anovulatory infertility, affecting up to 47% of patients. This work aims to present diagnostic methods, the importance of lifestyle management, and treatment methods in women with PCOS. Review Methods: A literature review was conducted using the PubMed database to identify relevant articles related to polycystic ovary syndrome (PCOS) using keywords: “Polycystic Ovary Syndrome”, “Polycystic Ovary Syndrome/diagnosis”, “Polycystic Ovary Syndrome/therapy”, “Phenotype”, “Infertility”, and “Life Style”. Brief description of the state of knowledge: PCOS typically presents with hyperandrogenism, polycystic ovarian morphology, and oligoovulation. It also affects metabolism, body weight, cardiovascular and mental health. Diagnosis is based on the modified Rotterdam criteria, which require two of three conditions: oligo/amenorrhea, hyperandrogenism, or polycystic ovaries, while excluding similar disorders. Treatment should be individualized and address infertility, menstrual disturbances, or androgen-related symptoms. Lifestyle interventions, including diet, regular physical activity, and weight control, are the first-line strategy in PCOS management. Summary: PCOS requires early diagnosis and individualized treatment tailored to the patient’s symptoms and reproductive goals. Lifestyle modifications, including diet and physical activity, play a key role in improving hormonal balance, metabolic health, and fertility outcomes in affected women.